SOSIALISASI PENCEGAHAN ASKFIKSIA NEONATORUM DI WILAYAH KERJA PKM TELAGA DEWA - maiseptyasari, ruri (Poltekkes Kemenkes Bengkulu, 2023)
Child mortality is a core indicator for child health and well-being. According to the world health organization the World Health Organization (WHO), globally, 2.4 million children died in the first month of life in 2019. There are approximately 7,000 newborn deaths every day, which account for 47% of all child deaths under the age of 5 years. Premature birth, intrapartum related complications (birth asphyxia or lack of breathing at birth), infections and birth defects account for the majority of neonatal deaths. this service is to increase the knowledge of pregnant women on the Prevention of Neonatal Asphyxia in the Telaga Dewa Health Center Work Area. This activity is distributing pre and post questionnaires, distributing leaflets and conducting socialization and finally evaluating activities.There is an increase in knowledge after the socialization where the average before the socialization is 30 increases to 75 after the socialization. From the activities that have been carried out, it is found that it is important for mothers to know the efforts to prevent asphyxia neonatorum from an early age for the birth of healthy babies and healthy mothers.